Diskontinuitas Bahasa Komunikasi Media Elektronik Dosen dan Mahasiswa Fakultas Agama Islam Universitas Muhammadiyah Malang - Thoifah, I’anatut (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
The issuance of regulations and appeals to the way of electronic media communication language in several universities are driven by lecturers' complaints about the number of communication from students via telephone, SMS, email, Whatsapp which is less ethical, in this case language plays an important role, the wording in non-communication Verbal through electronic media provides opportunities for considerable discontinuity in the meaning of sentences, because without visible intonation and expression, so it does not rule out the possibility of multi language interpretations of lecturers and students. This problem is said to be the generation difference is the reason for the creation of communication language discontinuity. This study aims to determine how the discontinuity and how the discontinuity forms of electronic media communication between lecturers and students. With descriptive qualitative research methods, the methods of data collection analysis, data condensation, display, and verification to find the results of the formulation of this research problem. The results observed are discontinuities in the language of communication between students and lecturers found in ways of communication that are not following the descriptive ethics intended by lecturers of the Faculty of Islamic Religion. The form of language discontinuity in student and lecturer communication is in the choice of diction.